Resolución espacial en la elaboración de mapas de ruido por interpolación Diego Mauricio Murillo Gómez (2017)
An analysis of the spatial resolution required for the noise measurement grid to generate noise maps based on interpolation methods is discussed. The process is based on the generation of reference cartography using the commercial package SoundPLAN. Subsequently, the results are exported as point receivers with different resolutions emulating in-situ measurements. These receivers are used to produce noise maps using interpolation techniques, which are compared to the respective reference. Low and densely populated environments have been considered in the current research. In addition, an evaluation using noise measurements from the Estadio’s neiborhood of the city Medellin is also presented. The outcomes indicate that the spatial resolution required to correctly represent the sound propagation depends on the complexity of the environment. For a general assessment, in which a global estimation of the acoustical condition is expected, a resolution of 80 m provides statistical representative information in urban scenes.